(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the features of the use of syntactic and compositional arts in artistic and scientific texts. Syntactic arts serve to increase the effectiveness of the text through sentence structure, word order, repetition and parallel constructions, while compositional arts ensure the overall structure, logical consistency and content integrity of the text. The study highlights the role of these types of art in increasing the expressiveness of speech, its psychological impact on the reader or listener, and its aesthetic value. It is also substantiated that the mutual harmony of syntactic and compositional means is an important factor in revealing the content of works of art more deeply. The article is of theoretical and practical importance for researchers conducting scientific research in the fields of linguistics and literary studies.